Efficient Triplet‐Triplet Annihilation Upconversion Sensitized by a Chromium(III) Complex via an Underexplored Energy Transfer Mechanism. (9th May 2022) - Wang, Cui; Reichenauer, Florian; Kitzmann, Winald R.; Kerzig, Christoph; Heinze, Katja; Resch‐Genger, Ute
Abstract: Sensitized triplet‐triplet annihilation upconversion (sTTA‐UC) mainly relies on precious metal complexes thanks to their high intersystem crossing (ISC) efficiencies, excited state energies, and lifetimes, while complexes of abundant first‐row transition metals are only rarely utilized and with often moderate UC quantum yields. [Cr(bpmp)2 ] 3+ (bpmp=2, 6‐bis(2‐pyridylmethyl)pyridine) containing earth‐abundant chromium possesses an absorption band suitable for green light excitation, a doublet excited state energy matching the triplet energy of 9, 10‐diphenyl anthracene (DPA), a close to millisecond excited state lifetime, and high photostability. Combined ISC and doublet‐triplet energy transfer from excited [Cr(bpmp)2 ] 3+ to DPA gives 3 DPA with close‐to‐unity quantum yield. TTA of 3 DPA furnishes green‐to‐blue UC with a quantum yield of 12.0 % (close to the theoretical maximum). Sterically less‐hindered anthracenes undergo a [4+4] cycloaddition with [Cr(bpmp)2 ] 3+ and green light. Abstract : The molecular ruby [Cr(bpmp)2 ] 3+ with an earth‐abundant chromium(III) central ion sensitizes green‐to‐blue triplet‐triplet annihilation upconversion with 9, 10‐diphenylanthracene as the annihilator. The process involves a near‐unity energy transfer efficiency via an underexplored reaction pathway, an anti‐Stokes shift of 0.54 eV, and a maximum upconversion quantum yield of 12.0 %.